2018
DOI: 10.1111/ijn.12677
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions of Chinese women with breast cancer and relationships with socio‐demographic and clinical characteristics

Abstract: These findings suggest that illness perceptions should be regarded as a whole to guide the coping process of Chinese women with breast cancer and provide new clinical information to support care for this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
2
7
1
Order By: Relevance
“…First, we could not include all the variables related to illness perception mentioned in previous studies. Considering that the study participants were cancer patients, we sought to minimize the fatigue from completing the questionnaires.6 Some other variables which could be included in future studies of illness perception are previous illness history, experience of breast cancer in the past (including serving as a caregiver for a family member or an important other with breast cancer), cultural aspects,36 disease knowledge,38 social socioeconomic status,35 and general life stress.34 Additionally, to explore the differences of disease experience by age, examining women’s sense of control or role functioning would be helpful. Second, the descriptive power of the models, which examined the factors influencing negative, positive, and total illness perception, was small.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we could not include all the variables related to illness perception mentioned in previous studies. Considering that the study participants were cancer patients, we sought to minimize the fatigue from completing the questionnaires.6 Some other variables which could be included in future studies of illness perception are previous illness history, experience of breast cancer in the past (including serving as a caregiver for a family member or an important other with breast cancer), cultural aspects,36 disease knowledge,38 social socioeconomic status,35 and general life stress.34 Additionally, to explore the differences of disease experience by age, examining women’s sense of control or role functioning would be helpful. Second, the descriptive power of the models, which examined the factors influencing negative, positive, and total illness perception, was small.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies have demonstrated how illness perception largely determines the sense of well-being in cancer patients, and breast cancer patients are no exception to this 1,6,7. The concept of illness perception has its foundation rooted in the self-regulation model by Leventhal and colleagues 8,9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that the illness perceptions of women with breast cancer differ according to the patient’s demographic and clinical factors. Better-educated women recognized more symptoms and younger women had more confidence in their ability to control the illness [ 19 ]. Patients who were not working perceived more-severe consequences, less treatment control, and stronger emotional impacts [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As age increases, the perception related to the concern that the illness will last for a longer time increase and the perception about the controllability of illness personally and with treatment decrease. Other studies show that the personal controls of young patients were higher (25,30). Young patients with BC have more worries regarding how they cope with their concerns about sexual dysfunction, their children, fertilization and body image (25).…”
Section: Discussionmentioning
confidence: 92%